Edukasi Publik Lintas Sektor tentang Kemiskinan, Pengangguran, dan Kriminalitas untuk Mendorong Kesadaran Pembangunan Ekonomi Berkelanjutan di Mandailing Natal - Jureid Jureid; Mufti Fahrizal Harahap; Faisal Affandi (Pemberdayaan Masyarakat : Jurnal Aksi Sosial, 2025)
This Community Service (PKM) activity aims to enhance public awareness of the interrelationship between poverty, unemployment, and criminality as key challenges to sustainable economic development in Mandailing Natal Regency. The program was conducted through a cross-sectoral seminar involving speakers from the District Attorney’s Office, the Central Bureau of Statistics (BPS), and local community organizations. A total of 120 participants—including students, lecturers, village officials, and the general public—took part in the event. Evaluation was carried out using pre-test and post-test questionnaires to measure participants’ improvement in understanding. The results showed an average increase in comprehension scores from 2.84 to 4.05 on a 1–5 scale (a 42.6 percent rise). Participants demonstrated greater awareness of the structural link between economic pressures and criminal behavior. This PKM activity successfully strengthened community understanding of the importance of inter-agency synergy in addressing poverty and unemployment as preventive measures against crime. Cross-sectoral public education proved effective in fostering social awareness and serves as a replicable model for other regions.